What philosophy is : contemporary philosophy in action - Carel, Havi; Gamez, David (Continuum, 2004)
What do we mean when we talk about philosophy today? How does philosophy relate to science, to politics, to literature? What methods does the modern philosopher use, and how does philosophy progress? Does philosophy differ from place to place? What can philosophy do for us? And what can it not do? This book, with contributions from such exciting and influential contemporary philosophers as Simon Blackburn, Michael Friedman, Simon Critchley and Manuel DeLanda, offers us a fascinating picture of the character and methods of philosophy; its possibilities and its limitations. And of course, it is.